Observations of energetic turbulence on the Weddell Sea continental slope - Fer, Ilker; Darelius, Elin; Daae, Kjersti B (Geophysical Research Letters, 2016)
Turbulence profile measurements made on the upper continental slope and shelf of the southeastern Weddell Sea reveal striking contrasts in dissipation and mixing rates between the two sites. The mean profiles of dissipation rates from the upper slope are 1–2 orders of magnitude greater than the profiles collected over the shelf in the entire water column. The difference increases toward the bottom where the dissipation rate of turbulent kinetic energy and the vertical eddy diffusivity on the slope exceed 10−7 W kg−1 and 10−2 m2 s−1, respectively. Elevated levels of turbulence on the slope are concentrated within a 100 m thick bottom layer, which is absent on the shelf. The upper slope is characterized by near-critical slopes and is in close proximity to the critical latitude for semidiurnal internal tides. Our observations suggest that the upper continental slope of the southern Weddell Sea is a generation site of semidiurnal internal tide, which is trapped along the slope along the critical latitude, and dissipates its energy in a 100 m thick layer near the bottom and within 10 km across the slope.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; havstrømmer; hydrografi; kontinentalsokkel

On the effect of topography and wind on warm water inflow—An idealized study of the southern Weddell Sea continental shelf system - Daae, Kjersti; Hattermann, Tore; Darelius, Elin; Fer, Ilker (Journal of Geophysical Research: Oceans, 2017)
An idealized eddy-resolving numerical model, with topographic features common to the southern Weddell Sea, is constructed to study mechanisms through which warm deep water enters a wide continental shelf with a trough. The open ocean, represented by a 1700 m deep channel, is connected to a 400 m deep shelf with a continental slope. The shelf is narrow (50 km) in the east but widens to 300 km at the center of the model domain. Over the narrow shelf, the slope front is balanced by wind-driven Ekman downwelling and counteracting eddy overturning, favoring on-shelf transport of warm water in summer scenarios when fresher surface water is present. Over the wide shelf, the Ekman downwelling ceases, and the mesoscale eddies relax the front. Inflow of warm water is sensitive to along-shelf salinity gradients and is most efficient when denser water over the wide shelf favors up-slope eddy transport along isopycnals of the V-shaped slope front. Inflow along the eastern side of the trough cannot penetrate the sill region due to potential vorticity constraints, while along the western trough flank, eddy-induced inflow crosses the sill and reaches the ice front. The warm inflow into the trough is sensitive to the density of the outflowing dense shelf water. For weaker winds, absence of the dense water outflow leads to a reversal of the trough circulation and a strong inflow of warm water, while for stronger winds, baroclinic effects become less important and the inflow is similar to experiments including dense water outflow.
Keywords: Sørishavet; Weddellhavet; batymetri; geofysikk; havstrømmer; hydrografi; klimamodeller; klimatologi; kontinentalsokkel; vannvirvler

Wind Stress Mediated Variability of the Filchner Trough Overflow, Weddell Sea - Daae, Kjersti Birkeland; Darelius, Elin Maria K; Fer, Ilker; Østerhus, Svein; Ryan, Svenja (Journal of Geophysical Research: Oceans, 2018)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Hydrography and circulation in the Filchner Depression, Weddell Sea, Antarctica - Darelius, Elin Maria K; Makinson, Keith; Daae, Kjersti Birkeland; Fer, Ilker; Holland, Paul R; Nicholls, Keith W (Journal of Geophysical Research: Oceans, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; havstrømmer; hydrografi; isfront; isshelf